Effects of Internet-Based Self-Efficacy Intervention on Secondary Traumatic Stress and Secondary Posttraumatic Growth among Health and Human Services Professionals Exposed to Indirect Trauma - Cieslak, Roman; Benight, Charles C.; Rogala, Anna; Smoktunowicz, Ewelina; Kowalska, Martyna; Zukowska, Katarzyna; Yeager, Carolyn; Luszczynska, Aleksandra (Frontiers in Psychology, 2016)
Background: Although the evidence for the associations among self–efficacy, secondary traumatic stress (STS) and secondary posttraumatic growth (SPTG) is mounting, there is a lack of the experimental evidence for the influence of self–efficacy on positive and negative mental health outcomes among professionals indirectly exposed to trauma. Purpose: This study investigated the effects of an internet–based self–efficacy intervention (the experimental condition), compared to an education (the active control condition) on STS and SPTG among workers exposed to traumatic events indirectly, through their clients. We hypothesized that the group assignment (experimental vs. control) would affect STS and SPTG indirectly, with a mediating role of self–efficacy beliefs. Methods: Participants were 168 health and human services professionals (78% women), exposed indirectly to a traumatic event at work. They were randomly assigned to either a 4–session internet–based self–efficacy intervention (n = 87) or an education control group (n = 81) which received information about coping resources and consequences of stressors at work or at home. STS, SPTG, and self–efficacy were measured at the baseline (Time 1), 1–month follow–up (Time 2) and 2–month follow–up (Time 3). Results: Analysis of covariance showed that the group assignment had a significant effect on STS (Time 2) and self–efficacy (Time 2), with lower STS and higher self–efficacy reported by the self–efficacy intervention participants. Compared to the experimental group, the active control (education) group participants reported higher SPTG at Time 2. Mediation analyses indicated that the group assignment had indirect effects on STS and SPTG at Time 3. Workers who experienced increases in self-efficacy (Time 2) through the intervention were more likely to report lower STS and higher SPTG at Time 3 Conclusions: Elucidating the mediating processes that explain why an intervention for secondary trauma works is essential in order to develop more effective support systems that promote improved mental health outcomes among health and human services professionals. Prevention programs for workers exposed indirectly to traumatic events may target self–efficacy enhancement and education.